Una dilatada bienvenida a la “normalidad”. Prácticas online en Cuba - Reloba de la Cruz, Xenia (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2021)
Cubans’ access to the Internet has been the subject of academic production and activism since the late 1990s. Until 2013, that right had only been exercised by about 25% of Cubans, according to official statistics. But since that year, ETECSA, a Cuban telecommunications company, has gradually increased the options for Wi-Fi, ADSL and mobile data access. Recent information indicates that about 75% of the Cuban population accesses the Internet through some of these channels. In addition, Cubans maintain alternative and irregular practices for accessing informational content. In this text, taking as a starting point an investigation carried out in the summer of 2018, I discuss the relationships between imaginaries about “modernity,” “normality,” “isolation” and “exceptionality,” in the context of the experiences of Cubans with information and communication technologies. My main argument is that by adopting and adjusting typically online practices to a mixed environment (online / offline), Cubans are rearticulating social imaginaries about modernity and the sense of belonging to the world historically associated with their identity, which shows a search for an “imagined” normality that subverts the feeling of isolation derived from technological backwardness.